EXTENSIONS OF VECTOR BUNDLES ON THE FARGUES-FONTAINE CURVE. (14th March 2022) - Birkbeck, Christopher; Feng, Tony; Hansen, David; Hong, Serin; Li, Qirui; Wang, Anthony; Ye, Lynnelle
Abstract: We completely classify the possible extensions between semistable vector bundles on the Fargues–Fontaine curve (over an algebraically closed perfectoid field), in terms of a simple condition on Harder–Narasimhan (HN) polygons. Our arguments rely on a careful study of various moduli spaces of bundle maps, which we define and analyze using Scholze's language of diamonds. This analysis reduces our main results to a somewhat involved combinatorial problem, which we then solve via a reinterpretation in terms of the Euclidean geometry of HN polygons.